2022
DOI: 10.3390/metabo13010010
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Zamia floridana A. DC. Leaves and Its Isolated Secondary Metabolites as Natural Anti-Toxoplasma and Anti-Cancer Agents Using In Vitro and In Silico Studies

Abstract: Toxoplasmosis and cancer are life-threatening diseases with worldwide distribution. However, currently used chemosynthetic treatments are not devoid of their own intrinsic problems. Natural metabolites are gaining attention due to their lower side effects. In this study, we investigated for the first time Zamia floridana leaves extract and its different fractions for their toxoplasmocidal activity, using Virulent RH Toxoplasma gondii, and cytotoxic activity against MCF-7 and HCT-116 cancer cell lines using MTT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…21 Bilobetin Bilobetin has a high binding affinity to (TSDHFR) with a docking score of -8.95 kcal/mol that explain the potent expected Toxoplasmocidal activity of this compound. 12 Bilobetin was found to exhibit significant antiproliferative activities against MCF-7 in a dosedependent manner with IC50 of 57.62 μg/mL 22 . In addition, the high docking score (-7.58 kcal/mol) of bilobetin against (CDK-2).…”
Section: Phytochemical Content Of Various Zamia Species and Their Bio...mentioning
confidence: 97%
See 4 more Smart Citations
“…21 Bilobetin Bilobetin has a high binding affinity to (TSDHFR) with a docking score of -8.95 kcal/mol that explain the potent expected Toxoplasmocidal activity of this compound. 12 Bilobetin was found to exhibit significant antiproliferative activities against MCF-7 in a dosedependent manner with IC50 of 57.62 μg/mL 22 . In addition, the high docking score (-7.58 kcal/mol) of bilobetin against (CDK-2).…”
Section: Phytochemical Content Of Various Zamia Species and Their Bio...mentioning
confidence: 97%
“…In silico docking study indicated that vicenin-2 has a significant inhibitory effect against the toxoplasma gondii parasite due to its high affinity toward thymidylate synthase reductase dihydrofolate reductase (TSDHFR) with high docking score of -8.74 kcal/mol. 12 Vicenin-2 has a significant affinity to a cyclindependent kinase target protein (CDK-2) using a docking study with high docking score of -8.38 kcal/mol which suggest that vicenin-2 may be used as a cytotoxic drug in cancer disease. 12 Amentoflavone Amentoflavone has a high docking score of -7.63 kcal/mol against (TSDHFR) using in silico experiment which proposed that amentoflavone can afford toxoplasmocidal activity.…”
Section: Phytochemical Content Of Various Zamia Species and Their Bio...mentioning
confidence: 99%
See 3 more Smart Citations